Synthesis of mesh-shaped calcia partially stabilized zirconia using eggshell membrane template as filler composite - Gempita, Gema; Hasratiningsih, Zulia; Subrata, Gantini; Purwasasmita, Bambang Sunendar (Faculty of Dentistry Universitas Padjadjaran, 2017)
Introduction: This experiment was conducted experimentally to synthesize Calcia Partially Stabilized Zirconia (Ca-PSZ) by sol-gel method using eggshell membrane template as a composite filler. The eggshell membrane was used to produce a mesh shaped structure, which hopefully can improve the mechanical properties of the composite. Method: Ca-PSZ filler was synthesized from ZrOCl2 precursor and Ca(NO3)2 stabilizer with a 24 hours immersion time. Ca-PSZ of synthesis then mixed with the resin matrix to test its composite hardness. Result: The EDS characterization results suggested that the sample contained elements of zirconia, calcium, and oxygen. Whereas, the XRD characterization identified that crystal structures that formed in the sample were nano scale tetragonal. Characterization of SEM showed Ca-PSZ with mesh structured. The average composite hardness value was 15.79 VHN. Conclusion: The composites with Ca-PSZ-synthesized filler could be prepared and its hardness value was higher than the composite with Ca-PSZ filler in spherical particles, but the hardness was still below the composite on the market.